1997
DOI: 10.1101/gad.11.20.2670
|View full text |Cite
|
Sign up to set email alerts
|

The Nun protein of bacteriophage HK022 inhibits translocation of Escherichia coliRNA polymerase without abolishing its catalytic activities

Abstract: Bacteriophage HK022 Nun protein blocks transcription elongation by Escherichia coli RNA polymerase in vitro without dissociating the transcription complex. Nun is active on complexes located at any template site tested. Ultimately, only the 3 -OH terminal nucleotide of the nascent transcript in an arrested complex can turn over; it is removed by pyrophosphate and restored with NTPs. This suggests that Nun inhibits the translocation of RNA polymerase without abolishing its catalytic activities. Unlike spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…It has been suggested that Nun may inhibit transcription elongation by blocking RNAP translocation (8). Using a combination of bulk biochemical and presteady-state approaches, we provide evidence that translocation inhibition is, in fact, the mode of Nun action.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…It has been suggested that Nun may inhibit transcription elongation by blocking RNAP translocation (8). Using a combination of bulk biochemical and presteady-state approaches, we provide evidence that translocation inhibition is, in fact, the mode of Nun action.…”
mentioning
confidence: 74%
“…Nun arrest results in the abrogation of λ transcription (8,19,20). E. coli Nus proteins facilitate Nun-mediated arrest both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15). Finally, Nun arrests transcription at many sites promoterdistal to NUT (21,22). This suggests that specific amino acidnucleotide interactions are not involved in Nun transcription In general, Nun proteins mutated at residues 106 and 107 are less active at nutR than at nutL.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal region makes contacts with the host NusA protein, RNA polymerase (RNAP), and DNA template (4)(5)(6). Nun induces transcription termination at sites just promoter-distal to nutL and nutR (1,7,8). Deletion of 13 C-terminal Nun amino acids stimulates NUT binding in vitro but abrogates transcription termination in vivo (6).…”
mentioning
confidence: 99%